Anti-counterfeiting digital invisible ink and application thereof

By using high-speed disperser, grinder and ultrasonic treatment methods in anti-counterfeiting inks, anti-counterfeiting digital invisible inks with invisible and manifesting effects, the problem of easy imitation and low color change temperature of existing anti-counterfeiting inks is solved, and the High stability and weather resistance of inks.

CN119410199AActive Publication Date: 2025-02-11SUNWAY PRECISION TECHNOLOGY (GUANGDONG) CO LTD

Patent Information

Application Number
CN202411854190.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-02-11
Estimated Expiration
2044-12-17

AI Technical Summary

Technical Problem

The existing anti-counterfeiting inks are not confidential when printing on substrates, they are easily imitated, and the color change temperature is too low and irreversible, making them prone to failure in natural storage.

Method used

The preparation method of anti-counterfeiting digital invisible ink is adopted. By dispersing the invisible anti-counterfeiting agent, polymer, stabilizer, solvent and additive evenly through a high-speed disperser, then send it to a grinder and then perform ultrasonic treatment. The obtained ink is prepared in The graphics and text information is displayed under specific lighting conditions, and has good stability and weather resistance.

Benefits of technology

The invisible effect and display effect of anti-counterfeiting labels are achieved, and the stability and weather resistance of the ink are improved. The settlement rate is low, the color rendering temperature is high, and the color rendering time is long, making it difficult to be illegally copied.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses anti-counterfeiting digital invisible ink and application thereof. The anti-counterfeit label provided by the invention is prepared by printing anti-counterfeit digital invisible ink on a label and heating and drying, and the anti-counterfeit digital invisible ink comprises the following raw material components in parts by mass: 10-40 parts of an invisible anti-counterfeit agent, 0.3-3 parts of a polymer, 0.05-1 part of a stabilizer, 5-30 parts of a solvent and 0.05-5 parts of an auxiliary agent, wherein the invisible anti-counterfeiting agent is selected from one of an invisible anti-counterfeiting core structure substance and core-shell composite particles; the raw material components are mixed, stirred and dispersed to obtain the anti-counterfeiting digital invisible ink. Compared with the prior art, the prepared anti-counterfeit label has the advantage of being good in invisible effect, and the adopted anti-counterfeit digital invisible ink has the advantages of being high in stability, good in weather resistance and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of printing inks, and in particular to an anti-counterfeiting digital invisible ink and its application. Background Art

[0002] "Anti-counterfeiting" mainly reflects prevention, and can provide solutions to counterfeiting from the source; "anti-counterfeiting" is universal, and can provide people with a usable way to distinguish authenticity in daily life. With the rapid development of social economy, various counterfeiting technologies are constantly upgraded and iterated, and counterfeiting in various manufacturing industries is becoming more and more serious, which will not only damage the interests of businesses, but also the interests of the country. In this context, effective anti-counterfeiting technical means are needed to provide protection for confidential document anti-counterfeiting, commodity anti-counterfeiting, and currency anti-counterfeiting, such as digital information anti-counterfeiting, biometric anti-counterfeiting, printing technology anti-counterfeiting, etc. Among them, anti-counterfeiting inks in printing technology anti-counterfeiting occupy an important position in printing technology anti-counterfeiting.

[0003] CN116200075A discloses a high-resolution anti-counterfeiting electronic ink and a preparation method thereof, which improves the color purity and the anti-counterfeiting performance of the ink by adding nano cadmium sulfide or nano titanium dioxide as nano anti-counterfeiting powder. However, the ink prepared by this method does not have a confidentiality effect when printed on a substrate and is easy to be imitated. CN114958092A discloses a temperature-changing anti-counterfeiting ink and a preparation method and application thereof, which is composed of 5-20 parts of color-changing material, 5-20 parts of acetic acid microcapsules, 30-50 parts of aqueous PUA emulsion, 15-30 parts of styrene acrylic resin and 5-30 parts of water. The prepared ink can change color in one direction at 37-45°C. However, the color change temperature of the ink prepared by this method is too low and irreversible, and it is easy to fail in natural storage. Summary of the invention

[0004] In view of the above-mentioned defects of the prior art, the present invention provides an anti-counterfeiting label prepared using anti-counterfeiting digital invisible ink. The anti-counterfeiting label prepared by the present invention has the advantages of good invisible effect, and the anti-counterfeiting digital invisible ink used has the advantages of high stability and good weather resistance.

[0005] To achieve the above object, the present invention provides a method for preparing an anti-counterfeiting digital invisible ink, comprising the following steps, measured by weight:

[0006] 10-40 parts of invisible anti-counterfeiting agent, 0.3-3 parts of polymer, 0.05-1 parts of stabilizer, 5-30 parts of solvent and 0.05-5 parts of auxiliary agent are dispersed evenly by a high-speed disperser, then sent to a grinder for grinding, and then ultrasonically treated to obtain anti-counterfeiting digital invisible ink.

[0007] Further preferably, the material is fed into a grinder and ground to a particle size of less than 10 μm, and the ultrasonic treatment condition is 40-100 kHz for 5-15 min.

[0008] Preferably, the polymer is selected from at least one of polyvinyl pyrrolidone, polyvinyl alcohol, polyethylene oxide, polyacrylamide, polyacrylic acid, polylactic acid, polyglycolic acid, polylactic acid-glycolic acid copolymer, polycaprolactone, polyethylene-vinyl acetate, polydimethylsiloxane and polyurethane.

[0009] The stabilizer is at least one of butyl mercaptan, nonyl mercaptan, dodecanethiol, hexadecyl mercaptan, thioglycolic acid, mercaptopropionic acid, 4-mercaptobutyric acid, 8-mercaptoheptanoic acid, 1-mercapto-2-propanone, 4-mercapto-2-pentanone, 3-mercapto-2-butanone, mercaptoethylamine, 3-mercapto-1-propylamine, and 3-mercapto-N-nonylpropionamide.

[0010] The solvent is selected from at least one of water, methanol, ethanol, isopropanol, n-propanol, ethylene glycol, propylene glycol, glycerol, n-butanol, n-octanol, n-nonanol, n-decanol, N-methylpyrrolidone, a mixture of dibasic acid esters, dimethylformamide, diacetone alcohol, 1,3-dimethyl-imidazolidinone, dimethyl sulfoxide, diethylene glycol monobutyl ether, diethylene glycol acetate, ethylene glycol carbonate, propylene glycol carbonate, 1,4-butyrolactone, toluene, chlorobenzene, dichloromethane, and tetrahydrofuran.

[0011] The auxiliary agent is selected from at least one of the perfluoro surfactants BOK-B-100, BOK-B-101, BOK-B-102 and BOK-B-103.

[0012] Further preferably, the solvent is a mixture of isopropanol and water in a mass ratio of 1-5:1-5.

[0013] Preferably, the invisible anti-counterfeiting agent is selected from one of invisible anti-counterfeiting core structure materials and core-shell composite particles.

[0014] Preferably, the preparation method of the invisible anti-counterfeiting core structure material comprises the following steps, measured by weight:

[0015] 1-5 parts of 1,3-dimethylbarbituric acid, 0.1-1.5 parts of furfural and 10-30 parts of water are mixed evenly, reacted at 20-40°C and 800-1000rpm for 1-3h, then the precipitate is collected and dissolved in dichloromethane, extracted with water and saturated sodium chloride, the organic phase is collected and the solvent is removed by a rotary evaporator to obtain compound 1; 1-5 parts of compound 1, 0.1-1.5 parts of diethylamine and 10-30 parts of water are mixed evenly, reacted at 20-40°C and 800-1000rpm for 1-3h, and then the solvent is removed by a rotary evaporator to obtain DASA, i.e., a donor-acceptor Steinhaus adduct molecule.

[0016] As a further illustration of the present invention, the donor-acceptor Steinhaus adduct molecule DASA can be mainly divided into two states, namely linear and cyclic, and these two states can be transformed into each other. The donor-acceptor Steinhaus adduct molecule DASA will transform from the initial colored state to a colorless closed-ring isomer under visible light, and is colorless under visible light and shows color under specific ultraviolet light; DASA can bind to water molecules and transform into a colorless and structurally stable cyclic donor-acceptor Steinhaus adduct hydrate. The cyclic donor-acceptor Steinhaus adduct hydrate will lose the bound water molecules when heated to about 160°C, and quickly transform into purple linear DASA in about 5s.

[0017] Preferably, the method for preparing the core-shell composite particles comprises the following steps, in parts by weight:

[0018] Step 1, 1-5 parts of 1,3-dimethylbarbituric acid, 0.1-1.5 parts of furfural and 10-30 parts of water are mixed evenly, reacted at 20-40°C and 800-1000rpm for 1-3h, then the precipitate is collected and dissolved in dichloromethane, extracted with water and saturated sodium chloride, and the organic phase is collected and the solvent is removed by a rotary evaporator to obtain compound 1; 1-5 parts of compound 1, 0.1-1.5 parts of diethylamine and 10-30 parts of water are mixed evenly, reacted at 20-40°C and 800 -1000rpm for 1-3h, then remove the solvent with a rotary evaporator to obtain DASA; add 5-15 parts of PAMAM dendritic polymer and 1-5 parts of DASA to 30-60 parts of tetrahydrofuran and mix evenly, then react at 60-100°C and 800-1000rpm for 2-4h; then centrifuge at 2000-4000rpm, collect the solid, and dry at 60-100°C for 4-8h to obtain core-structured DASA dendritic polymer microspheres;

[0019] Step 2: Mix 1-5 parts of silica with 5-10 parts of 5-15wt% HCl and stir for 1-3h, then centrifuge at 2000-4000rpm, collect solids, wash the solids with water until the supernatant is neutral, and dry the washed solids at 60-100°C for 4-8h to obtain activated silica; mix 1-5 parts of activated silica with 5-10 parts of ethanol, add 0.1-1 parts of ammonia water and 0.1-1 parts of silane coupling agent, react at 50-70°C, 800-1000rpm for 16-48h, then centrifuge at 2000-4000rpm, collect solids, wash the solids with ethanol until the supernatant is neutral, and dry the washed solids at 60-100°C for 4-8h to obtain modified silica;

[0020] Step 3: Mix 1-10 parts of modified silica in 10-50 parts of tetrahydrofuran, then add 5-10 parts of core structure DASA dendritic polymer microspheres, react at 20-60°C and 800-1000rpm for 2-4h, then centrifuge at 2000-4000rpm, collect the solid, and dry at 60-100°C for 4-8h to obtain composite modified silica, i.e. core-shell composite particles.

[0021] Further preferably, the step three may also be:

[0022] 1-10 parts of modified silica are mixed evenly in 10-50 parts of tetrahydrofuran, and then 5-10 parts of core structure DASA dendritic polymer microspheres are added, and the mixture is reacted at 20-60°C and 800-1000rpm for 2-4h, and then centrifuged at 2000-4000rpm, solids are collected, and dried at 60-100°C for 4-8h to obtain composite modified silica; 1-5 parts of composite modified silica and 1-50 parts of isopropanol are mixed evenly, and then 1-5 parts of phenolic resin are added, and then the mixture is reacted at 80-120°C and 800-1000rpm for 2-4h, cooled to room temperature, and then centrifuged at 2000-4000rpm, solids are collected, and the solids are dried at 60-100°C for 4-8h to obtain core-shell composite particles.

[0023] Further preferably, in the step 2, the silane coupling agent is selected from at least one of trimethoxy[2-(7-oxabicyclo[4.1.0]hept-3-yl)ethyl]silane.

[0024] As a further illustration of the present invention, the core-shell structure is a special composite material, which consists of a core (core) and one or more shells (shells) surrounding the core. PAMAM dendritic polymer has a unique topological structure and excellent temperature-sensitive properties, and can spontaneously assemble with DASA into microspheres as the core structure in the core-shell structure. The shell structure is a modified silica, a phenolic resin or a composition of modified silica and phenolic resin, which is assembled into core-shell composite particles through adsorption and / or chemical action. The use of silane coupling agents in the core-shell composite particles can promote the chemical bonding between the modified silica and the DASA dendritic polymer microspheres to form a stable core-shell structure, and the modified silica and phenolic resin may form a physical network structure in the particles. The shell of the core-shell structure can improve the dispersibility of the core in the ink, reduce particle aggregation, thereby improving the stability of the ink, and can also effectively limit the aggregation and sedimentation of particles. In addition, the shell of the core-shell structure may also form a protective layer on the surface of the particle, which can slow down the influence of external factors such as temperature, humidity, pH and other factors on the core, thereby improving the weather resistance and stability of the ink.

[0025] The present invention also provides the application of the anti-counterfeiting digital invisible ink on anti-counterfeiting labels. The specific application is as follows: the anti-counterfeiting label is printed on the label with the anti-counterfeiting digital invisible ink, and the printed content is invisible when prepared after drying at a temperature of 80-100°C for 1-3 hours, and the printed content appears purple after heating.

[0026] Beneficial effects of the present invention:

[0027] 1. Compared with the prior art, the present invention prepares anti-counterfeiting digital invisible ink by reasonable proportion and utilizing the interaction between various substances, and the anti-counterfeiting digital invisible ink is printed on the label to obtain an anti-counterfeiting label. The anti-counterfeiting digital invisible ink provided by the present invention not only has an invisible effect, but also displays graphic information under specific lighting conditions, so that traditional wearable labels have anti-counterfeiting characteristics, and also has good stability and acid and alkali resistance. The present invention introduces core-shell composite particles to prepare anti-counterfeiting digital invisible ink, which improves the stability of the ink. The anti-counterfeiting digital invisible ink prepared by the present invention is placed at 42±1°C for 21 days, and the sedimentation rate is only 0.99%.

[0028] 2. Compared with the prior art, the present invention adds core-shell composite particles during the preparation of the anti-counterfeiting digital invisible ink. Modified silica and phenolic resin are added to the core-shell composite particles at the same time, which may form a physical network structure in the core-shell composite particles, which can effectively limit the aggregation and sedimentation of the particles. After the anti-counterfeiting digital invisible ink of the present invention is placed at 42±1°C for 21 days, the sedimentation rate is only 0.99%, indicating that the ink of the present invention has better stability during storage and use.

[0029] 3. Compared with the prior art, the color development temperature of the label prepared by the anti-counterfeiting digital invisible ink of the present invention is 210°C and the color development time is 35 seconds, which is higher than the color development temperature of ordinary DASA and takes longer to develop. This means that the anti-counterfeiting label of the present invention is more difficult to be illegally copied because higher temperature and more precise conditions are required to show the printed content. DETAILED DESCRIPTION

[0030] The parameters and sources of some raw materials in the embodiments of the present invention are as follows:

[0031] Silicon dioxide, particle size: <150 μm;

[0032] Perfluorinated surfactant BOK-B-100, from Guangzhou Xinrui Chemical Materials Co., Ltd.;

[0033] Phenolic resin, brand: S607, from Jiangsu Senbo New Materials Co., Ltd.;

[0034] PAMAM dendrimer, product number: P475373, molecular weight 516.68, from Shanghai Aladdin Biochemical Technology Co., Ltd.;

[0035] Polyvinyl pyrrolidone, product number: P110611, average molecular weight 10000, from Shanghai Aladdin Biochemical Technology Co., Ltd.

[0036] Example 1

[0037] A method for preparing an anti-counterfeiting label using anti-counterfeiting digital invisible ink comprises the following steps:

[0038] Step a, 200g of invisible anti-counterfeiting core structure material, 10g of polyvinyl pyrrolidone, 2g of butanethiol, 200g of isopropanol, 50g of water, and 2g of perfluoro surfactant BOK-B-100 are dispersed uniformly by a high-speed disperser, and then sent to a grinder to grind to a particle size of less than 10μm, and then ultrasonically treated at 50kHz for 10min to obtain an anti-counterfeiting digital invisible ink;

[0039] Step b, printing the anti-counterfeiting digital invisible ink obtained in step a on a label, drying at a temperature of 90° C. for 2 hours, to obtain an anti-counterfeiting label with invisible printed content; after the anti-counterfeiting label is heated, the printed content appears purple.

[0040] The preparation method of the invisible anti-counterfeiting core structure material comprises the following steps:

[0041] 30 g of 1,3-dimethylbarbituric acid, 10 g of furfural and 200 g of water were mixed evenly, reacted at 30°C and 900 rpm for 2 h, then the precipitate was collected and dissolved in dichloromethane, extracted with water and saturated sodium chloride, the organic phase was collected and the solvent was removed by a rotary evaporator to obtain compound 1; 30 g of compound 1, 10 g of diethylamine and 200 g of water were mixed evenly, reacted at 30°C and 900 rpm for 2 h, then the solvent was removed by a rotary evaporator to obtain DASA; the invisible anti-counterfeiting core structure material was obtained.

[0042] Example 2

[0043] A method for preparing an anti-counterfeiting label using anti-counterfeiting digital invisible ink comprises the following steps:

[0044] Step a, each raw material component is calculated by mass, 200g of core structure DASA dendritic polymer microspheres, 10g of polyvinyl pyrrolidone, 2g of butanethiol, 200g of isopropanol, 50g of water, and 2g of BOK-B-100 are dispersed evenly by a high-speed disperser, and then sent to a grinder to grind to a particle size of less than 10μm, and then ultrasonically treated at 50kHz for 10min to obtain an anti-counterfeiting digital invisible ink;

[0045] Step b, printing the anti-counterfeiting digital invisible ink obtained in step a on a label, drying at a temperature of 90° C. for 2 hours, to obtain an anti-counterfeiting label with invisible printed content; after the anti-counterfeiting label is heated, the printed content appears purple.

[0046] The method for preparing the core structure DASA dendritic polymer microspheres comprises the following steps:

[0047] 30 g of 1,3-dimethylbarbituric acid, 10 g of furfural and 200 g of water were mixed evenly, reacted at 30°C and 900 rpm for 2 h, and then the precipitate was collected and dissolved in dichloromethane, extracted with water and saturated sodium chloride, and the organic phase was collected and the solvent was removed by a rotary evaporator to obtain compound 1; 30 g of compound 1, 10 g of diethylamine and 200 g of water were mixed evenly, reacted at 30°C and 900 rpm for 2 h, and then the solvent was removed by a rotary evaporator to obtain DASA; 100 g of PAMAM dendritic polymer and 30 g of DASA were added to 450 g of tetrahydrofuran and mixed evenly, and then reacted at 80°C and 900 rpm for 3 h; then centrifuged at 3000 rpm, the solid was collected, and dried at 80°C for 6 h to obtain core-structured DASA dendritic polymer microspheres.

[0048] Example 3

[0049] A method for preparing an anti-counterfeiting label using anti-counterfeiting digital invisible ink comprises the following steps:

[0050] Step a, 200g of core-shell composite particles, 10g of polyvinyl pyrrolidone, 2g of butanethiol, 200g of isopropanol, 50g of water, and 2g of BOK-B-100 are dispersed evenly by a high-speed disperser, and then sent to a grinder for grinding to a particle size of less than 10μm, and then ultrasonically treated at 50kHz for 10min to obtain an anti-counterfeiting digital invisible ink;

[0051] Step b, printing the anti-counterfeiting digital invisible ink obtained in step a on a label, drying at a temperature of 90° C. for 2 hours, to obtain an anti-counterfeiting label with invisible printed content; after the anti-counterfeiting label is heated, the printed content appears purple.

[0052] The method for preparing the core-shell composite particles comprises the following steps:

[0053] Step 1: 30 g of 1,3-dimethylbarbituric acid, 10 g of furfural and 200 g of water were mixed evenly, reacted at 30°C and 900 rpm for 2 h, and then the precipitate was collected and dissolved in dichloromethane, extracted with water and saturated sodium chloride, and the organic phase was collected and the solvent was removed by a rotary evaporator to obtain compound 1; 30 g of compound 1, 10 g of diethylamine and 200 g of water were mixed evenly, reacted at 30°C and 900 rpm for 2 h, and then the solvent was removed by a rotary evaporator to obtain DASA; 100 g of PAMAM dendritic polymer and 30 g of DASA were added to 450 g of tetrahydrofuran and mixed evenly, and then reacted at 80°C and 900 rpm for 3 h; then centrifuged at 3000 rpm, the solid was collected, and dried at 80°C for 6 h to obtain core-structured DASA dendritic polymer microspheres;

[0054] Step 2: Mix 30 g of silica with 80 g of 10 wt% HCl and stir for 2 h, then centrifuge at 3000 rpm, collect the solid, wash the solid with water until the supernatant is neutral, and dry the washed solid at 80 ° C for 6 h to obtain activated silica; 30 g of activated silica is evenly mixed with 80 g of ethanol, 5 g of ammonia water and 5 g of trimethoxy [2- (7-oxabicyclo [4.1.0] hept-3-yl) ethyl] silane are added, react at 60 ° C, 900 rpm for 24 h, then centrifuge at 3000 rpm, collect the solid, wash the solid with ethanol until the supernatant is neutral, and dry the washed solid at 80 ° C for 6 h to obtain modified silica;

[0055] Step 3: Mix 50 g of modified silica in 300 g of tetrahydrofuran, then add 80 g of core-structured DASA dendrimer microspheres, react at 40°C and 900 rpm for 3 h, then centrifuge at 3000 rpm, collect the solid, and dry at 70°C for 6 h to obtain composite modified silica, i.e., core-shell composite particles.

[0056] Example 4

[0057] A method for preparing an anti-counterfeiting label using anti-counterfeiting digital invisible ink, which is different from Example 2 in that the method for preparing the core-shell composite particles comprises the following steps:

[0058] Step 1: 30 g of 1,3-dimethylbarbituric acid, 10 g of furfural and 200 g of water were mixed evenly, reacted at 30°C and 900 rpm for 2 h, and then the precipitate was collected and dissolved in dichloromethane, extracted with water and saturated sodium chloride, and the organic phase was collected and the solvent was removed by a rotary evaporator to obtain compound 1; 30 g of compound 1, 10 g of diethylamine and 200 g of water were mixed evenly, reacted at 30°C and 900 rpm for 2 h, and then the solvent was removed by a rotary evaporator to obtain DASA; 100 g of PAMAM dendritic polymer and 30 g of DASA were added to 450 g of tetrahydrofuran and mixed evenly, and then reacted at 80°C and 900 rpm for 3 h; then centrifuged at 3000 rpm, the solid was collected, and dried at 80°C for 6 h to obtain core-structured DASA dendritic polymer microspheres;

[0059] Step 2: Mix 30 g of silica with 80 g of 10 wt% HCl and stir for 2 h, then centrifuge at 3000 rpm, collect the solid, wash the solid with water until the supernatant is neutral, and dry the washed solid at 80 ° C for 6 h to obtain activated silica; 30 g of activated silica is evenly mixed with 80 g of ethanol, 5 g of ammonia water and 5 g of N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane are added, react at 60 ° C and 900 rpm for 24 h, then centrifuge at 3000 rpm, collect the solid, wash the solid with ethanol until the supernatant is neutral, and dry the washed solid at 80 ° C for 6 h to obtain modified silica;

[0060] Step 3: Mix 50 g of modified silica in 300 g of tetrahydrofuran, then add 80 g of core-structured DASA dendrimer microspheres, react at 40°C and 900 rpm for 3 h, then centrifuge at 3000 rpm, collect the solid, and dry at 70°C for 6 h to obtain composite modified silica, i.e., core-shell composite particles.

[0061] Example 5

[0062] A method for preparing an anti-counterfeiting label using anti-counterfeiting digital invisible ink, which is different from Example 2 in that the method for preparing the core-shell composite particles comprises the following steps:

[0063] Step 1: 30 g of 1,3-dimethylbarbituric acid, 10 g of furfural and 200 g of water were mixed evenly, reacted at 30°C and 900 rpm for 2 h, and then the precipitate was collected and dissolved in dichloromethane, extracted with water and saturated sodium chloride, and the organic phase was collected and the solvent was removed by a rotary evaporator to obtain compound 1; 30 g of compound 1, 10 g of diethylamine and 200 g of water were mixed evenly, reacted at 30°C and 900 rpm for 2 h, and then the solvent was removed by a rotary evaporator to obtain DASA; 100 g of PAMAM dendritic polymer and 30 g of DASA were added to 450 g of tetrahydrofuran and mixed evenly, and then reacted at 80°C and 900 rpm for 3 h; then centrifuged at 3000 rpm, the solid was collected, and dried at 80°C for 6 h to obtain core-structured DASA dendritic polymer microspheres;

[0064] Step 2: Mix 30 g of silica with 80 g of 10 wt% HCl and stir for 2 h, then centrifuge at 3000 rpm, collect the solid, wash the solid with water until the supernatant is neutral, and dry the washed solid at 80 ° C for 6 h to obtain activated silica; 30 g of activated silica is evenly mixed with 80 g of ethanol, 5 g of ammonia water and 5 g of γ-mercaptopropyltrimethoxysilane are added, react at 60 ° C and 900 rpm for 24 h, then centrifuge at 3000 rpm, collect the solid, wash the solid with ethanol until the supernatant is neutral, and dry the washed solid at 80 ° C for 6 h to obtain modified silica.

[0065] Step 3: Mix 50 g of modified silica in 300 g of tetrahydrofuran, then add 80 g of core-structured DASA dendrimer microspheres, react at 40°C and 900 rpm for 3 h, then centrifuge at 3000 rpm, collect the solid, and dry at 70°C for 6 h to obtain composite modified silica, i.e., core-shell composite particles.

[0066] Example 6

[0067] A method for preparing an anti-counterfeiting label using anti-counterfeiting digital invisible ink, which is different from Example 2 in that the method for preparing the core-shell composite particles comprises the following steps:

[0068] Step 1: 30 g of 1,3-dimethylbarbituric acid, 10 g of furfural and 200 g of water were mixed evenly, reacted at 30°C and 900 rpm for 2 h, and then the precipitate was collected and dissolved in dichloromethane, extracted with water and saturated sodium chloride, and the organic phase was collected and the solvent was removed by a rotary evaporator to obtain compound 1; 30 g of compound 1, 10 g of diethylamine and 200 g of water were mixed evenly, reacted at 30°C and 900 rpm for 2 h, and then the solvent was removed by a rotary evaporator to obtain DASA; 100 g of PAMAM dendritic polymer and 30 g of DASA were added to 450 g of tetrahydrofuran and mixed evenly, and then reacted at 80°C and 900 rpm for 3 h; then centrifuged at 3000 rpm, the solid was collected, and dried at 80°C for 6 h to obtain core-structured DASA dendritic polymer microspheres;

[0069] Step 2: Mix 30 g of silica with 80 g of 10 wt% HCl and stir for 2 h, then centrifuge at 3000 rpm, collect the solid, wash the solid with water until the supernatant is neutral, and dry the washed solid at 80 ° C for 6 h to obtain activated silica; 30 g of activated silica is evenly mixed with 80 g of ethanol, 5 g of ammonia water and 5 g of trimethoxy [2- (7-oxabicyclo [4.1.0] hept-3-yl) ethyl] silane are added, react at 60 ° C, 900 rpm for 24 h, then centrifuge at 3000 rpm, collect the solid, wash the solid with ethanol until the supernatant is neutral, and dry the washed solid at 80 ° C for 6 h to obtain modified silica;

[0070] Step 3: Mix 50g of modified silica in 300g of tetrahydrofuran, then add 80g of core-structured DASA dendritic polymer microspheres, react at 40°C and 900rpm for 3h, then centrifuge at 3000rpm, collect the solid, and dry at 80°C for 6h to obtain composite modified silica; mix 25g of composite modified silica and 300g of isopropanol, add 25g of phenolic resin, then react at 100°C and 900rpm for 3h, cool to room temperature, then centrifuge at 3000rpm, collect the solid, and dry the solid at 80°C for 6h to obtain core-shell composite particles.

[0071] Comparative Example 1

[0072] A method for preparing an anti-counterfeiting label using anti-counterfeiting digital invisible ink, which is different from Example 2 in that the method for preparing the core-shell composite particles comprises the following steps:

[0073] Step 1: 30 g of 1,3-dimethylbarbituric acid, 10 g of furfural and 200 g of water were mixed evenly, reacted at 30°C and 900 rpm for 2 h, and then the precipitate was collected and dissolved in dichloromethane, extracted with water and saturated sodium chloride, and the organic phase was collected and the solvent was removed by a rotary evaporator to obtain compound 1; 30 g of compound 1, 10 g of diethylamine and 200 g of water were mixed evenly, reacted at 30°C and 900 rpm for 2 h, and then the solvent was removed by a rotary evaporator to obtain DASA; 100 g of PAMAM dendritic polymer and 30 g of DASA were added to 450 g of tetrahydrofuran and mixed evenly, and then reacted at 80°C and 900 rpm for 3 h; then centrifuged at 3000 rpm, the solid was collected, and dried at 80°C for 6 h to obtain core-structured DASA dendritic polymer microspheres;

[0074] Step 2: Mix 50 g of silica in 300 g of tetrahydrofuran, then add 80 g of core-structured DASA dendrimer microspheres, react at 40° C. and 900 rpm for 3 h, then centrifuge at 3000 rpm, collect the solid, and dry at 70° C. for 6 h to obtain core-shell composite particles.

[0075] Comparative Example 2

[0076] A method for preparing an anti-counterfeiting label using anti-counterfeiting digital invisible ink, which is different from Example 2 in that the method for preparing the core-shell composite particles comprises the following steps:

[0077] Step 1: 30 g of 1,3-dimethylbarbituric acid, 10 g of furfural and 200 g of water are mixed evenly, reacted at 30° C. and 800-1000 rpm for 1-3 h, and then the precipitate is collected and dissolved in dichloromethane, extracted with water and saturated sodium chloride, and the organic phase is collected and the solvent is removed by a rotary evaporator to obtain compound 1; 1-5 parts of compound 1, 0.1-1.5 parts of diethylamine and 10-30 parts of water are mixed evenly, reacted at 20-40° C. and 800-1000 rpm for 1-3 h, and then the solvent is removed by a rotary evaporator to obtain DASA; 100 g of PAMAM dendritic polymer and 30 g of DASA are added to 450 g of tetrahydrofuran and mixed evenly, and then reacted at 80° C. and 900 rpm for 3 h; then centrifuged at 3000 rpm, the solid is collected, and dried at 80° C. for 6 h to obtain core-structured DASA dendritic polymer microspheres;

[0078] Step 2: 50 g of phenolic resin and 300 g of tetrahydrofuran were mixed evenly, and then 80 g of core-structured DASA dendrimer microspheres were added, and the mixture was reacted at 40° C. and 900 rpm for 3 h, and then centrifuged at 3000 rpm, the solid was collected, and dried at 70° C. for 6 h to obtain core-shell composite particles.

[0079] Test Example 1

[0080] Stability test

[0081] 100 mL (V1) of the anti-counterfeiting digital invisible ink prepared in Examples 1-6 and Comparative Examples 1-2 were taken as test samples, respectively, and placed at 42±1° C. for 21 days. The sedimentation of the ink of each test sample was observed, and the unsettled volume (V2) was recorded. The ink sedimentation rate (S) was calculated according to the change in the ink sedimentation volume; the smaller the sedimentation rate, the better the stability of the ink; the calculation formula of the ink sedimentation rate is shown in the following calculation formula:

[0082] S = (V1-V2) / V1×100%;

[0083] Wherein, V1 is the initial volume, unit is mL; V2 is the unsettled volume, unit is mL; S is the sedimentation rate, %; the results are shown in Table 1.

[0084] Table 1 Sedimentation rate Project / No. Example 1 Example 2 Example 3 Example 4 Example 5 Example 6 Comparative Example 1 Comparative Example 2 Sedimentation rate (%) 3.36 3.13 2.26 2.67 2.43 0.99 2.95 2.24

[0085] By comparing Examples 1-6 with Comparative Examples 1-2, it can be found that the sedimentation rates of Examples 2-6 and Comparative Examples 1-2 are significantly lower than those of Example 1, wherein the sedimentation rate of Example 6 is the lowest at 0.99%. Analysis shows that the reason may be that the core-shell composite particles added in Example 6 have better dispersibility and stability.

[0086] By comparing Examples 2-5, it can be found that the sedimentation rate of Example 3 is lower than that of Examples 4 and 5. The reason may be that Example 2 is DASA dendritic polymer microspheres, and Example 3 uses β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane to modify silica to obtain modified silica. The silica surface modified with β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane can react with DASA dendritic polymer microspheres and hydroxyl groups or amino groups in the polymer to form covalent bonds, thereby enhancing the interaction between the polymer and silica, thereby improving the stability of the system; Examples 4 and 5 use N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane and γ-mercaptopropyltrimethoxysilane, which contain amino groups and mercapto groups, respectively, which can hydrogen bond with the hydroxyl groups on the surface of silica or form coordination bonds. Enhancing the interaction between silica and the polymer can also improve the stability of the system. Although the stability can be improved, the effect is lower than that of Example 3.

[0087] By comparing Examples 2-3, Example 6 and Comparative Examples 1-2, it can be found that compared with Example 2 in which the core-structured DASA dendritic polymer microspheres are introduced to prepare the invisible ink, Comparative Example 1 in which the core-structured DASA dendritic polymer microspheres and silica are introduced to obtain the ink of core-shell composite particles, and Comparative Example 2 in which the core-structured DASA dendritic polymer microspheres and phenolic resin are introduced to prepare the ink of core-shell composite particles, Example 6 in which the core-structured DASA dendritic polymer microspheres, modified silica and phenolic resin are simultaneously introduced to prepare the invisible ink of core-shell composite particles has the lowest sedimentation rate, only The stability is 0.99%, which is significantly higher than that of Comparative Example 1 and Comparative Example 2. The reason may be that the modified silica and phenolic resin may form a physical network structure in the core-shell composite particles, which can effectively limit the aggregation and sedimentation of the particles. The cross-linking points in the network structure can capture and fix the particles, reduce their free movement in the ink, and at the same time improve the overall chemical stability of the core-shell composite particles, reduce degradation during storage and use, thereby improving the stability of the ink. Adding silica or phenolic resin alone can improve the stability of the ink to a certain extent, but the effect is not as good as that of Example 6.

[0088] Test Example 2

[0089] Ink color development temperature and time test

[0090] The anti-counterfeiting digital invisible inks prepared in Examples 1-3, Example 6 and Comparative Examples 1-2 were printed on labels respectively, and the prepared labels were recorded as Example 1-3 group, Example 5 group and Comparative Example 1-2 group, respectively. Then, the labels of each group were heated to test the color development temperature and color development time of the labels; wherein the color development temperature refers to the temperature at which the color of the label changes, and the color development time refers to the time required for the label to color. The specific test results are shown in Table 2 below;

[0091] Ink acid and alkali resistance test

[0092] The anti-counterfeiting digital invisible inks prepared in Examples 1-3, Example 6 and Comparative Examples 1-2 were respectively used to prepare ink samples according to the standard "GB / T18724-2008 Printing Technology - Determination of Resistance of Printing Inks to Various Reagents", recorded as Example 1-3 group, Example 6 group and Comparative Example 1-2 group, and the acid and alkali resistance of each group of inks were tested according to the standard method of "GB / T18724-2008 Printing Technology - Determination of Resistance of Printing Inks to Various Reagents", and the test samples were qualified if there was no shedding, bubbling or discoloration; the specific test results are shown in Table 2 below.

[0093] Table 2 Group Example 1 Example 2 Example 3 Example 6 Comparative Example 1 Comparative Example 2 Color temperature (℃) 160 164 185 210 170 190 Color development time (s) 5 10 20 35 15 18 Acid resistance Failure qualified qualified qualified qualified qualified Alkali resistance Failure qualified qualified qualified qualified qualified

[0094] By comparing Examples 1-3, Example 6 and Comparative Examples 1-2, it can be found that compared with Example 2 in which the core-structured DASA dendritic polymer microspheres are introduced to prepare the invisible ink, Comparative Example 1 in which the core-structured DASA dendritic polymer microspheres and silica are introduced to prepare the ink of core-shell composite particles, and Comparative Example 2 in which the core-structured DASA dendritic polymer microspheres and phenolic resin are introduced to prepare the ink of core-shell composite particles, Example 6 simultaneously introduces the core-structured DASA dendritic polymer microspheres with modified silica and phenolic resin to prepare the invisible ink of core-shell composite particles. The color development temperature of the ink is 210°C, the color development time is 35s, and the acid and alkali resistance is qualified. The reason may be that modified silica and phenolic resin are added simultaneously during the preparation of the core-shell composite particles. The modified silica and phenolic resin may cross-link with the phenolic resin to form a physical network structure in the core-shell particles again. At the same time, a protective layer is formed on the surface. This protective layer can slow down the speed of heat transfer to the DASA molecules, so that a higher temperature and a longer time are required to achieve color development; at the same time, this protective layer can reduce the impact of external acid and alkali properties on the core and improve acid and alkali resistance. The core-shell structures of Comparative Examples 1-2 can form a protective layer to reduce the impact of external acid and alkali properties on the core, but are weaker than Example 6 in increasing the color development temperature and color development time.

Claims

1. A method for preparing an anti-counterfeiting digital invisible ink, characterized in that: The method comprises the following steps, calculated by weight: 10-40 parts of invisible anti-counterfeiting agent, 0.3-3 parts of polymer, 0.05-1 parts of stabilizer, 5-30 parts of solvent and 0.05-5 parts of auxiliary agent are dispersed evenly by a high-speed disperser, then sent to a grinder for grinding, and then ultrasonically treated to obtain anti-counterfeiting digital invisible ink.

2. The method for preparing the anti-counterfeiting digital invisible ink according to claim 1, characterized in that: The polymer is selected from at least one of polyvinyl pyrrolidone, polyvinyl alcohol, polyethylene oxide, polyacrylamide, polyacrylic acid, polylactic acid, polyglycolic acid, polylactic acid-glycolic acid copolymer, polycaprolactone, polyethylene-vinyl acetate, polydimethylsiloxane, and polyurethane; the stabilizer is selected from at least one of butanethiol, nonanethiol, dodecanethiol, hexadecanethiol, thioglycolic acid, mercaptopropionic acid, 4-mercaptobutyric acid, 8-mercaptoheptanoic acid, 1-mercapto-2-propanone, 4-mercapto-2-pentanone, 3-mercapto-2-butanone, mercaptoethylamine, 3-mercapto-1-propylamine, and 3-mercapto-N-nonylpropionamide; the solvent is selected from at least one of At least one of water, methanol, ethanol, isopropanol, n-propanol, ethylene glycol, propylene glycol, glycerol, n-butanol, n-octanol, n-nonanol, n-decanol, N-methylpyrrolidone, a mixture of dibasic acid esters, dimethylformamide, diacetone alcohol, 1,3-dimethyl-imidazolidinone, dimethyl sulfoxide, diethylene glycol monobutyl ether, diethylene glycol acetate, ethylene glycol carbonate, propylene glycol carbonate, 1,4-butyrolactone, toluene, chlorobenzene, dichloromethane, and tetrahydrofuran; the auxiliary agent is selected from at least one of the perfluorinated surfactants BOK-B-100, BOK-B-101, BOK-B-102, and BOK-B-103.

3. The method for preparing the anti-counterfeiting digital invisible ink according to claim 1, characterized in that: The invisible anti-counterfeiting agent is selected from one of invisible anti-counterfeiting core structure materials, core structure DASA dendritic polymer microspheres, and core-shell composite particles.

4. The method for preparing the anti-counterfeiting digital invisible ink according to claim 3, characterized in that: The preparation method of the invisible anti-counterfeiting core structure material comprises the following steps, calculated by weight: 1-5 parts of 1,3-dimethylbarbituric acid, 0.1-1.5 parts of furfural and 10-30 parts of water are mixed evenly, reacted at 20-40°C and 800-1000rpm for 1-3h, then the precipitate is collected and dissolved in dichloromethane, extracted with water and saturated sodium chloride, the organic phase is collected and the solvent is removed by a rotary evaporator to obtain compound 1; 1-5 parts of compound 1, 0.1-1.5 parts of diethylamine and 10-30 parts of water are mixed evenly, reacted at 20-40°C and 800-1000rpm for 1-3h, and then the solvent is removed by a rotary evaporator to obtain DASA, i.e., an invisible anti-counterfeiting core structure material.

5. The method for preparing the anti-counterfeiting digital invisible ink according to claim 3, characterized in that: The preparation method of the core-shell composite particles comprises the following steps, calculated by weight: Step 1, 1-5 parts of 1,3-dimethylbarbituric acid, 0.1-1.5 parts of furfural and 10-30 parts of water are mixed evenly, reacted at 20-40°C and 800-1000rpm for 1-3h, then the precipitate is collected and dissolved in dichloromethane, extracted with water and saturated sodium chloride, and the organic phase is collected and the solvent is removed by a rotary evaporator to obtain compound 1; 1-5 parts of compound 1, 0.1-1.5 parts of diethylamine and 10-30 parts of water are mixed evenly, reacted at 20-40°C and 800 -1000rpm for 1-3h, then remove the solvent with a rotary evaporator to obtain DASA; add 5-15 parts of PAMAM dendritic polymer and 1-5 parts of DASA to 30-60 parts of tetrahydrofuran and mix evenly, then react at 60-100°C and 800-1000rpm for 2-4h; then centrifuge at 2000-4000rpm, collect the solid, and dry at 60-100°C for 4-8h to obtain core-structured DASA dendritic polymer microspheres; Step 2: Mix 1-5 parts of silica with 5-10 parts of 5-15wt% HCl and stir for 1-3h, then centrifuge at 2000-4000rpm, collect solids, wash the solids with water until the supernatant is neutral, and dry the washed solids at 60-100°C for 4-8h to obtain activated silica; mix 1-5 parts of activated silica with 5-10 parts of ethanol, add 0.1-1 parts of ammonia water and 0.1-1 parts of silane coupling agent, react at 50-70°C, 800-1000rpm for 16-48h, then centrifuge at 2000-4000rpm, collect solids, wash the solids with ethanol until the supernatant is neutral, and dry the washed solids at 60-100°C for 4-8h to obtain modified silica; Step 3: Mix 1-10 parts of modified silica in 10-50 parts of tetrahydrofuran, then add 5-10 parts of core structure DASA dendritic polymer microspheres, react at 20-60°C and 800-1000rpm for 2-4h, then centrifuge at 2000-4000rpm, collect the solid, and dry at 60-100°C for 4-8h to obtain composite modified silica, i.e. core-shell composite particles.

6. The method for preparing the anti-counterfeiting digital invisible ink according to claim 5, characterized in that: The silane coupling agent in step 2 is selected from at least one of trimethoxy[2-(7-oxabicyclo[4.1.0]hept-3-yl)ethyl]silane, N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane, and γ-mercaptopropyltrimethoxysilane.

7. The method for preparing the anti-counterfeiting digital invisible ink according to claim 5, characterized in that: The step three can also be: uniformly mixing 1-10 parts of modified silica with 1-50 parts of tetrahydrofuran, then adding 5-10 parts of DASA dendritic polymer microspheres, reacting at 20-60°C and 800-1000rpm for 2-4h, then centrifuging at 2000-4000rpm, collecting solids, and drying at 60-100°C for 4-8h to obtain composite modified silica; uniformly mixing 1-5 parts of composite modified silica and 1-50 parts of isopropanol, adding 1-5 parts of phenolic resin, then reacting at 80-120°C and 800-1000rpm for 2-4h, cooling to room temperature, then centrifuging at 2000-4000rpm, collecting solids, and drying the solids at 60-100°C for 4-8h to obtain core-shell composite particles.

8. Anti-counterfeiting digital invisible ink prepared by the method according to any one of claims 1 to 7.

9. The use of the anti-counterfeiting digital invisible ink on the anti-counterfeiting label as claimed in claim 8, characterized in that: The anti-counterfeiting label is printed on the label with anti-counterfeiting digital invisible ink. When it is prepared after drying at a temperature of 80-100° C. for 1-3 hours, the printed content is invisible, and after heating, the printed content appears purple.

Citation Information

Patent Citations

  • Temperature-variable anti-counterfeiting ink as well as preparation method and application thereof

    CN114958092A

  • Photochromic anti-counterfeiting bar code and preparation method thereof

    CN111849248A

  • Preparation method of silicon dioxide nanoparticles capable of converting surface polarity through visible light response

    CN112898803A

  • Multi-arm block type polycaprolactone color-changing polymer and preparation method thereof, and light-operated color-changing sponge and preparation method thereof

    CN113980208A

  • Preparation method of bidirectional light-operated core-shell structure nanoparticles based on DASAs

    CN115068621A

Cited By

  • Anti-counterfeiting digital invisible ink and application thereof

    WO2026129652A1